Penyakit Anthracnose pada eili Di Malaysia: Biologi Patogen dan Varietal Susceptibility - Saadon, Mazlan; Meon, Sariah (1980)
Studies on the biology of Colletotrichum capsici showed growth and sporulation were at maxima at 30°C and pH 5. Among the media used, Bean Pod Agar and Potato Dextrose Agar were more conducive for growth while Lima Bean Agar was most conducive for sporulation. Cultures receiving continuous normal light and normal light alternated with ultra violet gave better growth while those exposed to diurnal treatment gave better sporulation. Glasshouse trials showed that variety C10 was most susceptible to anthracnose when compared to the other varie ties tested. VarietY' C1 showed the highest tolerance level to anthracnose.